This is who I am: a phenomenological analysis of female purity pledgers' sense of identity and sexual agency - Hanna, Katrina N. (Kansas State University, 2016)
At the turn of the 21st century, an ideological movement defined by many as the modesty movement helped push sexual abstinence as a controversial yet significant public issue in the United States. Concerned with a "hyper-sexualized" culture, modesty advocates urged young women to make a pledge to remain pure until marriage. Following the the growth of the movement, feminist scholars have been critical of the movement and the potentially detrimental consequences of purity pledges on young women's identity, sexuality, and sexual agency. This study takes a step back from this critical view of purity pledges and listens to young women's lived experience of making a purity pledge and living a life of purity. Specifically, this study asks how purity pledgers understand and enact purity and how they perceive their sexuality and sexual agency. To answer these questions, qualitative interviews were conducted with nine young women who at some point in their life made a purity pledge. A thematic analysis revealed three major themes: 1) living a pure life is situated within multifaceted perspectives on purity, 2) living a life of purity consists of negotiating multiple "selves," and 3) living a life of purity grants and reinforces a sense of agency. A composite description illustrates that religious messages, parents, peers, and sex education classes continue to influence their understanding of purity and sexuality. This project concludes with a discussion of theoretical implications surrounding the idea of a "crystallized self" and practical implications of this study on an organizational, familial, and personal level.
Keywords: Purity; Purity pledge; Sexuality; Sexual agency; Identity; Crystallized self